Implementasi Kepemimpinan, Motivasi, dan Budaya Organisasi Kaitannya dengan Profesionalisme Karyawan Tetap - Aditya Wisnu Wardhana; Sampeadi Sampeadi; Chairul Saleh (Jurnal Ekonomi Akuntansi dan Manajemen, 2019)
This study has two objectives. First, describe the implementation of leadership, motivation, and organizational culture in relation to the professionalism of permanent employees. Second, analyze the relationship of leadership, motivation and organizational culture with the professionalism of permanent employees. The object of research is Bank Jatim, Jember Branch. This study uses descriptive and expalanatory design. The population is 47 permanent employees of Bank Jatim, Jember Branch. The sampling method used is a saturated sample technique which is included in nonprobability sampling. With saturated sample techniques, the entire population is used as the research sample. Data collection is done through survey and observation methods. The analytical method used is descriptive statistical analysis and correlation analysis of Kendall Tau. Keywords: Leadership, Motivation, Organizational Culture, Profesionalism